Pengaruh Gaya Kepemimpinan, Pelatihan Dan Pengembangan Dan Kompetensi Terhadap Kinerja - Leni Marlina; Deni Fajar Insani; Abdul Ajiz; Darsa Darsa (E-Journal Studia Manajemen, 2022)
This study aims to obtain information regarding whether performance is influenced by leadership style, training and development and competence. Using a causal study through a survey of PKH program facilitators in Lebak Regency, Indonesia, for a sample of 46 employees, data for each variable were collected separately by respondents who filled out the questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression. The results prove that there is an influence of leadership style on performance, there is an influence of training and development on performance, there is an influence of competence on performance, and there is an influence of leadership style, training and development and competence together on performance. These findings indicate that organizations need to consider the variables of leadership style, training and development, and competence in human resource planning and development of the Lebak District PKH program facilitators.